Aesthetics of symbols in the culture of the Turks and their existential-meaning-life basis (Journal of Philosophy Culture and Political Science, 2018)
The authors, making a review of the symbols of Turkic culture and studying the sources and ideological bases of its origin, analyze vitally-practical aspects of Turkic culture. Examines the values of numbers in a symbolic reflection of the worldview of ancient Turkic peoples, artistic creative vision of the world in a numerical sense. Is defined threefold vertical structure of the world in religious beliefs, ancient legends and suggests ideas inner essence of this hierarchical system. Shown ethical and aesthetic aspects ofthese ideas. The article, based on a review of one of the ontological characters of ancestors depicting theworld – a sacred tree, are disclosed various forms of understanding. Since the «tree of peace» refers to thegreatness and ontologi-anthropological value of a single tree in the valley, which has survived since theancient era. Further, it is considered mystical-mythological and symbolic-aesthetic meaning of beginningof mountains, which is associated with «balbaltas». Finale, authors come to the conclusion that the set ofsymbols of the individual elements of ancient Turkic worldview is a holistic view of the world.Key words: mythology of the Turks, traditional worldview of the Turks, Turk`s culture, archetype, symbol, sacredness, aesthetics.